The Determinant of Internet Financial Reporting: Evidence From Asean Stock Exchange - Angela Angela; Dyna Rachmawati (JAFFA, 2021)
This research aims to analyze the effect of profitability, liquidity, leverage, and market activity on Internet Financial Reporting (IFR). This research was conducted at consumer goods sub-sector manufacturing companies listed on the ASEAN Stock Exchange in 2018-2019. This research used the purposive sampling method. The samples consisted of 378 companies. The data analysis technique used in this research is multiple linear regression analysis techniques. Based on the results of the analysis, it can be seen that the profitability variable has a positive effect on IFR, while the liquidity variable has a negative effect on IFR, then leverage and market activity have no effect on internet financial reporting, where greater leverage and market activity do not make the present company information on internet financial reporting.